Changes in gelatinisation and pasting properties of various starches (wheat, maize and waxy maize) by the addition of bacterial cellulose fibrils - Díaz-Calderón, P.; Macnaughtan, William; Hill, Sandra; Foster, Tim; Enrione, Javier; Mitchell, John (Elsevier, 2018)
The aim of this work was to analyse the effect of bacterial cellulose fibrils (BCF) on the gelatinization profile and pasting properties of starches from different sources (wheat, maize and waxy maize) and amylose contents. Blends of 8% starch with different BCF levels (0, 0.5, 2, 6 and 10% based on the dry weight of starch) were prepared and tested by Rapid Visco-Analysis (RVA), Differential Scanning Calorimetry (DSC) and both Optical and Polarized Light Microscopy. Results showed that BCF produce a significant modification of pasting properties. The pasting temperature was reduced but viscosities (peak, final, trough, breakdown and final) increased. The reduction in pasting temperature at the highest BCF addition was 200C higher for maize and wheat starches but only 20C higher for waxy maize starch. In contrast to the pasting temperature, the gelatinisation temperature by DSC for all three starches slightly varied upon BCF addition, but the gelatinisation enthalpy was reduced to a greater extent than values reported for the addition of other hydrocolloids to starch blends. Optical and polarized light microscopy showed the presence of domains rich in starch and highly aggregated BCF in all three starches evaluated. The increase in viscosity and decrease in pasting temperature are discussed in terms of changes in starch concentrations in the starch rich domain. These results open interesting perspectives in the use of bacterial cellulose and plant cell walls to design novel bio-composites to structure foods.